ANALISIS PERSEDIAAN BAHAN BAKU PADA PRODUKSI TAHU PAK BAMBANG DI KECAMATAN SAMARINDA ULU KOTA SAMARINDA - Negara, Andre Abdini (EKONOMIA, 2019)
Andre Abdini Negara: Analysis of Inventory of Raw Materials in Tahu Pak Bambang Production in Samarinda Ulu District, Samarinda City. Under the guidance of Mr. H. Eddy Soegiarto K. and Mrs. Andi Indrawati.This research was conducted to find out whether the amount of purchases or orders of soybean raw materials made by home industries tahu Pak Bambang was economical, and whether the frequency of buying or ordering soybean raw materials made by home industries Tahu Pak Bambang was optimal.The analysis used in this study is an analysis of the optimal number of purchases or orders, the frequency of economical purchases or orders, and total inventory costs based on the Economic Order Quantity (EOQ) method and then compared with calculations according to home industry.Based on the results of the analysis, it is known that the amount of raw material purchase or order of tofu production in the form of soybeans that has been carried out by home industry Tahu Mr. Bambang during the period of January to April 2019 is not yet economical. Besides that, the frequency of buying or ordering raw materials for tofu production in the form of soybeans that have been carried out by home industries Tahu Mr. Bambang during the period of January to April 2019 is not optimal, as well as the total cost of raw material production in the form of soybeans issued by the home industry Tahu Mr. Bambang that during the period of January to April 2019 was higher than the total cost of soybean raw material supplies based on the Economic Order Quantity (EOQ) method